INFLUENCE OF WORK LIFE BALANCE AND BURNOUT ON THE LEVEL OF EMPLOYEE JOB SATISFACTION AT PT. COLUMBUS CASH & CREDIT PAREPARE BRANCH - Firgiawan, Ariel Ahmad; Sahabuddin, Romansyah; Nurman, Nurman (Jurnal Manajemen, 2025)
Abstract: Ariel Ahmad Firgiawan, 2025. The influence of work life balance and burnout on the level of employee job satisfaction at PT. Columbus Cash & Credit Parepare branch. Thesis. Management Study Program. Faculty of Economics and Business. Makassar State University. This study aims to determine the effect of work life balance and burnout on the level of employee job satisfaction at PT. Columbus Cash & Credit Parepare branch. The variables in this study consist of independent variables, namely work life balance and burnout, and the dependent variable, namely job satisfaction. The research method uses a quantitative approach with multiple linear regression analysis. Data collection techniques in the form of observation, interviews, and questionnaires distributed to 30 respondents. This study uses SPSS software version 27 as proof of the hypothesis. The results of this study indicate that good work life balance has a significant effect on employee job satisfaction and bad burnout has a negative impact on job satisfaction.Keywords: Work Life Balance, Burnout, and Job Satisfaction.